ANALISIS PENGGUNAAN MAJAS PADA PUISI BERJUDUL AKU CEMBURU, SELALU KAMU, DAN JARAK KARYA PRILLY LATUCONSINA - Khofifatul Anfa'ah Rachman; Teti Sobari; Dede Abdurrokhman (IKIP Siliwangi, 2022)
Poetry is a literary work that needs to be appreciated and assessed for its beauty. This assessment can be seen from the characteristics or uniqueness created by a writer when writing poetry. This becomes important to analyze so that everyone can know the characteristics or uniqueness contained in a literary work. This research intends to examine the use of a figure of speech in three poems by Prilly Latuconsina. The descriptive qualitative approach is a method chosen and used in this research. The researcher conducted an analytical study by understanding and examining the figures of speech in these poems. The result of the research states that the poems by Prilly Latuconsina have their characteristics or uniqueness. This characteristic can be seen from the use of figures of speech in the three poems. As for the figures of speech contained in the poem, namely, consisting of personification figures, similes, metaphors, and repetitions.